Differential effects of Moodle course design on student subpopulations: advancing personalized learning in higher education - Serhiy O. Semerikov; Pavlo P. Nechypurenko; Tetiana A. Vakaliuk; Iryna S. Mintii; Liliia O. Fadieieva (Smart Learning Environments)
Abstract Higher education institutions face increasing challenges in meeting the diverse needs of their student populations. While learning management systems (LMS) like Moodle have become ubiquitous in higher education, there remains limited understanding of how these platforms affect different student subpopulations. This study investigates the differential effects of Moodle course design elements on student outcomes across key demographic dimensions: form of education (full-time versus part-time) and educational level (undergraduate versus graduate). Using structural equation modeling and a dataset of 3684 courses from a European university (2020–2022), we identified significant differences in how Moodle components affect learning outcomes across student subgroups. Interactive activities and communication tools showed substantially stronger relationships with outcomes for part-time students, while comprehensive information and resources demonstrated stronger impacts for graduate students. We introduce a theoretical framework for personalization effects in LMS environments and identify specific design elements that promote more equitable outcomes across student subpopulations. This research addresses critical gaps in our understanding of personalized learning in higher education, providing evidence-based guidance for instructors and instructional designers seeking to create more inclusive, effective digital learning environments that respond to the specific needs of diverse student populations.